Mobile laboratory "Explosive destruction of natural materials": Investigation of the behavior of ice and limestone under explosive loading; Journal of Physics: Conference Series; Vol. 653 : Interaction of Intense Energy Fluxes with Matter (ELBRUS 2015) - Orlov M. Yu. Maksim Yurjevich (2015, 2015)
Title screen